Octacyano-substituted tridecacyclene: a non-benzenoid cyanocarbon with low-lying LUMO and multistage redox properties - Misselwitz, Erik; Spengler, Jonas; Rominger, Frank; Kivala, Milan (Chemical communications, 2025)
Octacyanated tridecacyclene was synthesized from novel brominated tridecacyclene. In the crystal, the saddle-shaped scaffold exhibits a zigzag packing motif governed by an interplay between the inherent geometry of the central cyclooctatetraene moiety and the hydrogen bonding mediated by the dipolar cyano functionalities. The compound undergoes five reversible reductions in a particularly narrow potential window of 1.15 V in CH2Cl2. The first reduction occurs at −0.78 V (vs. Fc/Fc+), which corresponds to a remarkably low-lying LUMO of −4.32 eV.